Impact of Pregnancy Anemia and Low Birth Weight on Toddler Stunting - Nanda Febyani; Yetti Anggraini; Yuliawati Yuliawati (Jurnal Kesehatan, 2026)
Stunting is a long-term nutritional disorder among children under five that negatively affects physical growth, cognitive performance, and overall human resource quality in later life. Maternal health during pregnancy plays a critical role in the occurrence of stunting, with maternal anemia and low birth weight (LBW) identified as major contributing factors. This study aimed to examine the association between maternal anemia during pregnancy and LBW with stunting among children aged under five in the working area of Metro City. This study employed an observational-analytical design with a cross-sectional approach. The subjects consisted of mothers and children aged 24–59 months who met the specified inclusion criteria. A total of 60 respondents were selected using total sampling and purposive sampling techniques. Data were analysed using univariate and bivariate analyses, with the chi-square test to assess the relationships between variables. The findings demonstrated a statistically significant association between a history of maternal anemia during pregnancy and stunting (p = 0.012). Likewise, LBW was significantly associated with stunting (p = 0.004). Children born with LBW and those whose mothers experienced anemia during pregnancy were found to have a higher likelihood of developing stunting compared to children without such risk factors. In summary, maternal anemia during pregnancy and LBW are significantly associated with stunting among children under five. Therefore, stunting prevention strategies should prioritize strengthening antenatal care services, enhancing early detection and management of maternal anemia, and implementing adequate nutritional interventions for pregnant women to reduce the risk of LBW and subsequent stunting.